(untitled) (The International Journal for Scientific Research, 2024)
The study aimed to identify the impact of strategic vigilance within the Saudi Ministry of Communications and Information Technology on performance and its environmental sustainability, and to reveal statistically significant differences between the responses of the study sample members according to the variable (gender - age group - qualifications - job title - number of years of experience), and to achieve these goals. The descriptive analytical method was used, and the researcher built a questionnaire for this purpose, consisting of (38) items, and the study sample consisted of (285) individuals. The study reached many results, the most important of which are: The members of the study sample believe that strategic vigilance is not practiced to a high degree in the ministry, and that technological vigilance, as a dimension of strategic vigilance, has a high impact on performance. Considering this, the researcher presented his recommendations, including establishing a system for strategic vigilance. Officially within the Ministry, because the special changes force it to adapt to them and keep up with them, in order to achieve the ability to make effective decisions and confront future challenges, establishing executive units for strategic vigilance that are included within the organizational structure of the Ministry, and equipped with the necessary material, human and technical capabilities so that they are able to carry out the function. Strategic vigilance